The NHS Health Check in England: an evaluation of the first 4 years - Robson, John; Dostal, Isabel; Sheikh, Aziz; Eldridge, Sandra; Madurasinghe, Vichithranie; Griffiths, Chris; Coupland, Carol; Hippisley-Cox, Julia (BMJ Publishing Group Ltd, 2016)
Objectives: To describe implementation of a new national preventive programme to reduce cardiovascular morbidity.